Improving the efficiency of engines for large nonfighter aircraft - National Research Council (U.S.). Committee on Analysis of Air Force Engine Efficiency Improvement Options for Large Non-fighter Aircraft; National Research Council (U.S.). Air Force Studies Board (Washington, D.C. : National Academies Press, 2007)
19